Horticultura no baixo curso do Rio Doce, zona norte do Natal/RN: avaliação da qualidade da água por meio de ensaios ecotoxicológicos - Moura, Wanessa Kaline de Araújo (2011)
The research is developed in areas of horticulture in the city of Natal, in the neighborhoods of Lagoa Azul, Pajuçara and Redinha, along the Doce River, border area with Extremoz city, Rio Grande do Norte State. The region of the fluvial plain of Doce River is located in an Environmental Protection Zone (ZPA-9). This is one of the ZPA which is not under the regulatory marks and there are several environmental problems caused by use and land occupation, featuring an evident disregard of environmental laws and whose protection is hindered by the lack of specific legal mechanisms. This study aims to provide an overview of the use of pesticides in the lower course of the Doce River, in Natal, Rio Grande do Norte, and to assess environmental degradation in the area through chronic toxicity tests using the microcrustaceous Ceriodaphnia dubia Richard 1894 (Cladocera, Crustacea) as test organism. Visits were made to the area in 2009 and 2010. To obtain information a diagnosis of the local situation was accomplished based on personal observation and non-participatory photographic record, with the aim of assessing the environmental characteristics, population diversity and work processes of horticulturists. During the visits four different points of the Doce River were chosen to collect water for ecotoxicological tests and survey of physico-chemical parameters (dissolved oxygen, pH, chloride, turbidity, conductivity and temperature), which were measured in the field using Multiparameter Probe (TROLL 9500). The adverse effects of pesticide use in the lower course of the Doce River is a major problem for both the environmental and human health, since many of the substances and active principles that enter in the composition of the products are synthesized molecules whose effects can only be evaluated through different studies on their actions and behavior at short, medium or long term